Performance evaluation of a locally fabricated crusher (hammer mill) (2002)
A bone-crusher (Hammer Mill) was designed, constructed and tested. The machine was designed to crush 1000kg of bones in one hour. The motor operating speed employed is 2920rpm, the sieve hole diameters are 7mm and 5mm while the numbers of hammers are 12 and 18 pieces. The performance tests show that the mill is capable of crushing between 860 to 1170kg within an hour.